2015
DOI: 10.1002/jat.3201
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis is repressed by ethanol exposure during chick embryonic development

Abstract: It is now known that excess alcohol consumption during pregnancy can cause fetal alcohol syndrome to develop. However, it is not known whether excess ethanol exposure could directly affect angiogenesis in the embryo or angiogenesis being indirectly affected because of ethanol-induced fetal alcohol syndrome. Using the chick yolk sac membrane (YSM) model, we demonstrated that ethanol exposure dramatically inhibited angiogenesis in the YSM of 9-day-old chick embryos, in a dose-dependent manner. Likewise, the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 45 publications
1
39
0
2
Order By: Relevance
“…In our previous studies, excess reactive oxygen species (ROS) generation played an important role in angiogenesis defects (Jin et al, 2013;Li et al, 2014;Wang et al, 2015b). Therefore, we next studied the effect of excess ROS generation.…”
Section: The Formation Of Blood Islands In the Extraembryonic Region mentioning
confidence: 98%
See 1 more Smart Citation
“…In our previous studies, excess reactive oxygen species (ROS) generation played an important role in angiogenesis defects (Jin et al, 2013;Li et al, 2014;Wang et al, 2015b). Therefore, we next studied the effect of excess ROS generation.…”
Section: The Formation Of Blood Islands In the Extraembryonic Region mentioning
confidence: 98%
“…Hypoxia activates hypoxia inducible factor-1 and 2-alpha (HIF-1α and HIF-2α) and could induce vessels to branch towards the hypoxic tissue (Pugh and Ratcliffe, 2003). Reactive oxygen species (ROS), as a component of oxidative phosphorylation, also play an important role in regulation of HIF-1α (Hagen, 2012), VEGF (Xia et al, 2007), FGF2 (Wang et al, 2015b), cardiovascular system (Brown and Griendling, 2015) and embryonic development (Dennery, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In our previously study, excess ethanol exposure was shown to inhibit embryonic angiogenesis through promoting superfluous ROS production during embryo development [40]. A.C. Tufan and N.L.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in previous publications, ethanol exposure can induce excess ROS production [34,40]. 2,2-azobis (2-amidinopropane) dihydrochloride (AAPH, a free radicals generator 25, 40) was used to establish whether excess ROS could also induce vascular malformation and also in combination with vitamin C (an depressor of ROS production) to see whether the ethanol-or AAPH-induced inhibitive effect can be rescued (Figs.…”
Section: Ethanol Exposure Causes Excess Ros Generation During Blood Imentioning
confidence: 99%
“…The morphology of the CAMs was photographed. The areas occupied by the blood vessel were measured by Intel Integrated Performance Primitives (IPP) [14]. The blood vessel density was the percentage of area occupied by the blood vessels over the whole area under the picture's field [15].…”
mentioning
confidence: 99%